Characteristics of Glycemic Variability in Patients with GCK-MODY - A. K. Ovsyannikova; M. V. Dudina; Yu. A. Dolinskaya; O. D. Rymar (SINAPS LLC, 2022)
GCK-MODY is one of the most common MODY variants (40-60 %) in the European population. It is possible to use continuous glucose monitoring systems (CGMS) when diagnosing GCK-MODY which allows for an analysis of glucose variability (GV) using mathematical indices and a detailed assessment of the glycemic profile. The purpose of this abstract is to investigate the features of GV in young people with GCK-MODY. A daily study of glucose levels was performed using portable systems for CGMS in 20 patients (7 men and 13 women, median age at diagnosis of DM was 28.0 [18.0; 36.0] years) with a mutation in the glucokinase gene confirmed by molecular genetic testing. There was also performed an analysis of glycemic variability indices with the specialized GLINVA program. Most patients with GCK-MODY have target values when determining routine indicators of carbohydrate metabolism (fasting plasma glucose (FPG) and glycated hemoglobin), they determines the tactics of managing patients from this group of patients (rational nutrition or minimal doses of oral hypoglycemic drugs). However, after conducting CGMS and studying the GV indices it was determined that in some patients the indices were higher than the reference values with normal levels of glycated hemoglobin and FPG, and it is this group of patients that needs therapy correction. The results demonstrate a flat glycemic profile during the day which probably causes a lower incidence of diabetic complications and determines the tactics of GCK-MODY patient management.